SLIS AND SLOS DEMYSTIFIED;A WORKSHOP APPROACH TO BUILDING AND MAINTAINING YOUR SERVICE LEVEL INDICATORS AND SERVICE LEVEL OBJECTIVES - ALEXANDRA F. MCCOY (PACKT PUBLISHING, 2025)
Master reliability engineering with SLIs and SLOs to optimize performance, enhance observability, and make data-driven decisions Key Features Design precise SLIs and SLOs tailored to different system architectures and reliability goals Master observability techniques and incident management strategies to proactively detect and resolve issues Build scenario-based SLIs and SLOs with hands-on guidance for real-world reliability engineering Purchase of the print or Kindle book includes a free PDF eBook Book Description In today's digital landscape, ensuring service reliability is more than just a necessity--it's a competitive advantage. SLIs and SLOs Demystified equips software engineers, SREs, and business leaders with the knowledge to build, measure, and manage service level indicators (SLIs) and service level objectives (SLOs) efficiently. Written by Alexandra F. McCoy--an experienced site reliability engineer with over a decade of experience in the cloud and technology industry--this book simplifies complex reliability concepts for engineers at all levels. Starting with a review of reliability engineering basics, Alexandra provides a step-by-step approach to defining impactful SLIs, facilitating productive SLO discussions, and integrating observability into your monitoring strategy. You'll also see how these principles apply to web applications, distributed systems, databases, and new features through real-world examples that can help you develop SLIs and SLOs for your specific environment. The book goes beyond implementation to explore the financial impact of reliability, alerting strategies, integration with incident management, and using error budgets for business decisions. By the end of this book, you'll be able to drive operational excellence, minimize unplanned downtime, and optimize end user experiences with well-established reliability metrics. What you will learn Formulate and implement SLIs and SLOs for assessing and enhancing system reliability objectives Manage incidents proactively using observability and monitoring Create adequate reliability metrics for complex systems Refine incident response strategies to minimize associated risks Align reliability objectives with business and technical goals Implement strong reliability practices across multiple teams and services Integrate reliability engineering with DevOps and site reliability engineering practices Who this book is for This book is designed for site reliability engineers (SREs), DevOps engineers, software engineers, product managers, and business leaders looking to enhance service reliability to ensure their applications meet performance expectations. Basic knowledge of cloud services, system monitoring, and software engineering principles is beneficial.